Empire's proxy : American literature and U.S. imperialism in the Philippines - Wesling, Meg (America and the long 19th century., 2011)
In the late nineteenth century, American teachers descended on the Philippines, which had been newly purchased by the U.S. at the end of the Spanish-American War. Motivated by President McKinley's project of "benevolent assimilation," they established a school system that centered on English language and American literature to advance the superiority of the Anglo-Saxon tradition, which was held up as justification for the U.S.'s civilizing mission and offered as a promise of moral uplift and political advancement. Meanwhile, on American soil, the field of American literature was just being developed and fundamentally, though invisibly, defined by this new, extraterritorial expansion